Institutional Ownership, Newly Appointed CEO, and Dividend Initiation - Rahmat Setiawan; Erry Wisudawan Pradana (Universitas Hayam Wuruk Perbanas, 2019)
The purpose of this study is to examine the effect of institutional ownership on dividend initiation with newly appointed CEO holding a role as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange. This research used a logistic regression model and Moderated Regression Analysis (MRA). The data were obtained from the public company's Financial Report and Annual Report published in the 2012-2017 period. Dividend initiation is the dependent variable measured using dummy variable, and institutional ownership is the independent variable proxied by the percentage of shares held by institutional investors. Newly appointed CEO is the moderating variable. The result shows that institutional ownership has a significant positive effect on dividend initiation and the newly appointed CEO strengthens the positive effect of institutional ownership on dividend initiation. It is advisable that the companies should improve their corporate governance’s quality by increasing the degree on institutional ownership.